Prediction of Repeat Visits by Victims of Intimate Partner Violence to a Level III Trauma Centre. (14th November 2012) - Janssen, Patricia; Mackay, Kathleen
Abstract : Background . The purpose of this study was to describe and contrast the population of persons presenting to a Vancouver hospital emergency department two or more times with those presenting once. Methods . Subjects for this study had disclosed intimate partner violence on at least one visit to Vancouver General Hospital Emergency Department during the study period 1997–2009. We compared sociodemographic characteristics, presenting complaints and disposition on discharge among single versus repeat visitors. Results . We identified 2246 single visitors and 257 repeat visitors. In a multivariate model, repeat visitors to the ER were more likely to be of First Nations (aboriginal) status, odds ratio (OR) 2.29, 95% confidence intervals (1.30–4.01); to have had a history of previous abuse 3.38 (1.88–6.08); to have received threats of homicide 2.98 (1.74–5.08); and to present with mental illness 3.03 (1.59–5.77). Police involvement was protective against repeat visits 0.54 (0.36–0.98). Conclusion . Persons with potential for multiple visits to the emergency room can be characterized by a number of factors, the presence of which should trigger targeted assessment for violence exposure in settings where assessment is not routine.